Informal Employment in Urban China : Measurement and Implications - Park, Albert; Wu, Yaowu; Du, Yang (World Bank, Washington, DC, 2017)
Because of China's socialist legacy, until recently little attention has been paid to the rise of informal employment. Under planning urban workers enjoyed guaranteed employment, housing, pensions, and health care. The prevalence of informal employment has important implications for public policies, because informality is often associated with poverty and social vulnerability, and it affects tax collection, the enforcement of labor regulations, and the provision of adequate social protection to workers and their families. Informality thus can be characterized by dualism, including both those who engage in informal work of their own volition and those who do so involuntarily because they are systematically excluded from formal employment opportunities. The goal of this paper is to provide for the first time an accurate measurement of informal employment in China by analyzing data from recent household surveys collected in six large Chinese cities in 2010. The surveys were designed by the authors with questions included to enable measurement of informality using accepted international standards set by the International Labour Organization (ILO) as well as by considering factors relevant in the Chinese context. The authors provide a number of insights into the extent and nature of informal employment and labor market development in China. The large payroll charges for social insurance programs create a disincentive for both employers and employees to participate.